Produktivitas Sufiks -te dan -shu dalam Bahasa Jepang - Lestari, Ni Putu Wulan; Widya Purnawati, Ketut; Andry Anita Dewi, Ni Made (Humanis; Vol 26 No 1 (2022), 2022)
This study is a corpus-based analysis that aims to investigate the productivity of the -te and -shu suffixes as agent-forming suffixes in Japanese as well as the structure of noun formation by adding these two suffixes. The theories used in this research are the theory of productivity by Baayen (1992) and the theory of Japanese morphology by Tsujimura (2013). Based on the results of the analysis on the Japanese News 2020 100K corpus, it was found that the suffix -te is more productive as a form of agent nominals. The suffix -te when attached to an infinitive verb denotes a person who conducts a certain action while the suffix -shu when attached to a Sino-Japanese verbal noun, noun, or bound morphemes denotes one’s profession .